Stylised facts of economic growth in developing countries - Thomas M. Steger (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2001)
This paper offers a concise survey on the literature of growth empirics applying to DCs. It is argued that there is a number of important stylised facts of economic growth relevant to DCs which are not included in the corresponding lists of Kaldor and Romer. In contrary to the usual procedure, the growth rates of per capita income are calculated by employing potential output, which is determined by the use of the Hodrick-Prescott-filter. Finally, three important conclusions resulting from the empirical observations are discussed in the last section.
Keywords: O10; O40; O47; 330; Stylised Facts; Economic Growth; Developing Countries; Growth Empirics; Wirtschaftswachstum; Entwicklung; Entwicklungsländer; Korrelation